(Un-) healthy ageing: Geographic inequalities in disability-free life expectancy in England and Wales. (July 2022) - Norman, Paul; Exeter, Dan; Shelton, Nicola; Head, Jenny; Murray, Emily
Abstract: Health expectancies are an indicator of healthy ageing that reflect quantity and quality of life. Using limiting long term illness and mortality prevalence, we calculate disability-free life expectancy for small areas in England and Wales between 1991 and 2011 for males and females aged 50–74, the life stage when people may be changing their occupation from main career to retirement or alternative work activities. We find that inequalities in disability-free life expectancy are deeply entrenched, including former coalfield and ex-industrial areas and that areas of persistent (dis-) advantage, worsening or improving deprivation have health change in line with deprivation change. A mixed health picture for rural and coastal areas requires further investigation as do the demographic processes which underpin these area level health differences. Highlights: Poor area level health in old coalfield and ex-industrial areas is deeply entrenched. Areas of persistent (dis-)advantage or worsening or improving deprivation have concomitant health change. Socio-demographic attributes associated with area health disadvantage are multifaceted. A mixed health picture for rural and coastal areas requires specific research.